The asymmetric spillover effects of retirement on disability: evidence from China - Bai, Anying; Hao, Zhuang; Cheng, Huihui; Chen, Simiao; Jiang, Yu (Innovation in Aging, 2024)
Recent research has explored the spillover effects of retirement on spousal well-being, yet limited attention has been given to the short-term impact on spousal disability. This study explored the asymmetric spillover impact of retirement on spouses’ disability severity among a national cohort of urban residents in China.Utilizing 4 waves of data (2011-2018) from the China Health and Retirement Longitudinal Survey, we employ a nonparametric regression discontinuity design to estimate the short-term effect of retirement on spousal disability severity. Disability is assessed based on their ability to perform activities of daily living (ADLs) and instrumental activities of daily living (IADLs). Furthermore, we conduct heterogeneity analysis stratified by factors such as the husband’s retirement status, health conditions, lifestyle behaviors, and the wife’s educational level. Additionally, we explore potential mechanisms including changes in health behaviors, emotions, and disease diagnoses.Our findings indicate that wives’ retirement has a significant favorable short-term effect on husbands’ ADL scores, with a magnitude of −0.644 points (−9.78% relative to baseline). A significant beneficial effect of wives’ retirement on the prevalence of husbands’ difficulty in dressing, bathing, and eating was observed with substantial magnitudes of 0.075, 0.201, and 0.051 points, respectively. Various heterogeneity analyses and sensitivity tests confirmed the robustness of our results. The positive spillover effect of wives’ retirement likely results from reduced negative emotions in husbands. In contrast, husbands’ retirement does not affect the prevalence of ADL/IADL disability in their wives.Underscoring the gender asymmetry in the effects of spousal retirement on disability, this study emphasizes the need for tailored policies considering men’s and women’s distinct disability experiences.
Online veröffentlicht: 23. August 2024
Gesehen am 26.03.2025